If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 1 + -1(-1x) = x Remove parenthesis around (-1x) x + 1 + -1 * -1x = x Multiply -1 * -1 x + 1 + 1x = x Reorder the terms: 1 + x + 1x = x Combine like terms: x + 1x = 2x 1 + 2x = x Solving 1 + 2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + 2x + -1x = x + -1x Combine like terms: 2x + -1x = 1x 1 + 1x = x + -1x Combine like terms: x + -1x = 0 1 + 1x = 0 Add '-1' to each side of the equation. 1 + -1 + 1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 0 + -1 1x = 0 + -1 Combine like terms: 0 + -1 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| 3/-5b-1/10=7/20-7/10b | | -10=-(m+6) | | 2k^2-50=0 | | (7x-7)(x+5)= | | x-1=6x-31 | | 2x-3=x2/3 | | 5=-3n-1+n | | V=-2v+80 | | tan(50)=x/20 | | -x+6=-8+6x | | f(x)=(x+2)(x+1)(x-5) | | 2(h-4)=8 | | 8(t-4)=40 | | 10n-2-3n=19 | | 3+3n+4=16 | | -3(6+3k)=-18+7k | | 2x-1=5x+6 | | 8y-6y=12-8 | | 4(x+1)+2x=4+x+1+4+1+2+x+2+2 | | 1/2x26 | | -3k-34=4(k-5) | | 2x-3+4x=15 | | 9+5m=-6 | | .17x-0.43=.25k+0.05 | | 50=x-(x*0.054+0.3) | | 0=-5v-4v | | -8(1+3x)=40-8x | | 2n-126=-4n | | n+n-6=38 | | 5(7+5v)=v+35 | | 3x+6=G | | 19x+7=19x+7 |